2021
DOI: 10.2217/bmm-2020-0669
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Incident Heart Failure in Older Men: the Role of Nt-Probnp

Abstract: Aim: To determine the relationship between baseline inflammation (CRP and IL-6) with natriuretic peptide (NP) activity (measured by NT-proBNP) and incident heart failure (HF) in older men. Methods & results: In the British Regional Heart Study, 3569 men without prevalent myocardial infarction or HF were followed for mean 16.3 years; 327 developed HF. Baseline CRP and IL-6 were significantly and positively associated with NT-proBNP. Those in the highest CRP & IL-6 quartiles had elevated risk of HF after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…There are many clinical scoring and biomarkers that are used to determine the prognosis in post-MI patients. Related studies have been carried out separately for each other marker which was used, in our study, and it has been determined that these markers can provide with valuable prognostic information [13], [14], [15], [16], [17], [18], [19]. In a recently published study on association between NT-proBNP and 12 months MACE in NSTEMI patients, it was concluded that NT-proBNP represents a long-term prognostic biomarker for high-risk MACE in the first 12 months after NSTEMI, especially for older patients and those with reduced LVEF [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many clinical scoring and biomarkers that are used to determine the prognosis in post-MI patients. Related studies have been carried out separately for each other marker which was used, in our study, and it has been determined that these markers can provide with valuable prognostic information [13], [14], [15], [16], [17], [18], [19]. In a recently published study on association between NT-proBNP and 12 months MACE in NSTEMI patients, it was concluded that NT-proBNP represents a long-term prognostic biomarker for high-risk MACE in the first 12 months after NSTEMI, especially for older patients and those with reduced LVEF [14].…”
Section: Discussionmentioning
confidence: 99%
“…Khan states that a multibiomarker approach improves cardiac risk prediction, stratification, including MACE after MI [15]. Recently published study, set to determine the relationship between inflammation, natriuretic peptides, and incident HF in older men [16], suggests that increased levels of NT-proBNP are associated with markers of inflammation and the risk of HF. According to Oleynikov et al, increased levels of NT-proBNP are prognostic factors for HF progression in patients surviving STEMI [18].…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP i hs-CRP su povezani sa drugim inflamatornim biomarkerima, kao što su IL-6 i pojava srčane insuficijencije kod starijih muškaraca [20,21].…”
Section: Discussionunclassified
“…NT-proBNP and hs-CRP are linked to other inflammatory biomarkers, such as IL-6 and heart failure in older men [20,21].…”
Section: Biomarkerimentioning
confidence: 99%
“…In the literature, it is stated that chronic activation of the immune system plays a central role in the occurrence and progression of HF with reduced ejection fraction and HF with preserved ejection fraction (5). It has been shown that there is a correlation between inflammation and adverse cardiovascular events in patients with HF, and inflammation plays a prominent role in both acute and chronic heart failure (1).…”
Section: Introductionmentioning
confidence: 99%